Degree of satisfaction among hearing aid users - Mondelli, Maria Fernanda Capoani Garcia; Rocha, Andressa Vital; Honório, Heitor Marques (International Archives of Otorhinolaryngology, 2013)
Introduction: Hearing loss (HL) is defined as the complete or partial loss of hearing ability. Aims: To characterize (1) the degree of satisfaction among adult and elderly hearing aid (HA) users who were treated by a public hearing health service and (2) the relationship between satisfaction and the variables of gender, age, degree of HL, and type of HA. Method: The clinical and experimental study included the administration of the Satisfaction with Amplification in Daily Life (SADL) questionnaire to 110 patients who had used HAs for more than 3 months and were 18 years of age or older. Results: Test patients were sex-balanced (48% were women) and had a mean age of 67 years. A relatively high incidence of sensorineural moderate HL was detected in the study patients (66%) and device B was the most commonly used HA type (48%). No significant differences were evident between HA satisfaction and sex. The importance placed on services/costs and personal image varied between age groups. Correlation was evident at all levels between user satisfaction and amplification. Decreased satisfaction was observed in individuals with severe and/or profound HL. The type of HA used yielded statistically significant differences in the positive effects referring. Conclusion: No correlations were evident between the different factors proposed. HA users exhibited high levels of satisfaction in all SADL areas.
Keywords: hearing loss; hearing aids; patient satisfaction